Isolamento e identificação molecular da microbiota predominante na fermentação natural de mandioca: seleção de culturas iniciadoras para produção de polvilho azedo em escala piloto - Fernanda Correa Leal Penido (2013)
Sour cassava starch is obtained from the natural fermentation of cassava in a spontaneous process conducted by microorganisms present in raw materials and fermentation tanks. The producer evaluates the end of the fermentation empirically, which leads to a process without any standardization and to the achievement of inferior quality products. This product is used primarily in the baking industry for the manufacture of biscuits and Brazilian cheese breads. It represents an alternative to gluten, which should be avoided by people with celiac disease. The objective of this work was to isolate and identify molecularly the predominant microbiota of cassava fermentation, in order to select microbial strains to be used as starter cultures for the production of sour cassava starch in a pilot study. The samples were collected in a cassava flour manufacturer in Formiga (MG) during 40 days of fermentation. Lactic acid bacteria (LAB) were prevalent throughout the whole process and yeasts appeared in significant proportions since the beginning of the process remaining until the 26th day of fermentation. The predominant BAL represented mainly the genus Lactobacillus and Lactobacillus brevis was the most frequent isolated. Pichia scutulata was the predominant yeast. From the 19th to the last day of fermentation, the pH of the fermentation tank decreased and consequently the values of total titratable acidity (TTA) increased. Regarding the tests for selection of starter cultures, P. scutulata had the largest number of isolates with amylolytic activity and Lb. brevis produced higher values of TTA in the acidification test, Lactobacillus plantarum also showed significant values. The species Lb. brevis, Lb. plantarum and P. scutulata were selected to be tested as pure and mixed starter cultures in a pilot study. The fermentation was conducted during 28 days and it was verified that the peak of acidity and the lower pH value happened on the 7th day of fermentation. The BAL remained viable throughout the whole pilot study fermentation, while the yeasts remained for 7 to 14 days. Lb. plantarum showed better performance as starter culture and the results suggest this BAL presents the potential to be used in a pure or mixed starter culture for the production of sour cassava starch.